A Study on Models and Foundations for Nation-Building: An Analysis from the Lense of Prophetic Sirah - Aroos, Ashker; Ashath, Mohamed (Yayasan Cendekia Gagayunan Indonesia, 2025)
Nation-building is a concept that is widely discussed in the modern world. Today, various disciplines are studying its guidelines. Although guidelines for this can be found in the sources of Islam such as the Quran and Sunnah, this is an attempt to find its practical form in the Sirah of the Prophet (P.B.U.H). He was a messenger of God and as well a great nation-builder and the society he created is still admired by scholars today. In the secular environment where religion and state are constructed as two poles, the examples of the Prophet (P.B.U.H) are important. Against this background, this study explains through practical events that the Prophet (P.B.U.H) protected the nation's values in Mecca, Abyssinia, and Medina and guided the Muslims. For this purpose, primary sources and research articles on the Sirah have been considered and a discussion has been built. As a result, this study emphasizes that Muslims, whether they live in the minority or the majority, in the country where they were born and raised or in the country where they gained fame, should contribute to the country they live in and establishes that it is included in the tasks of 'Imarah' and 'Khilafah' that man must fulfill in the world from the Quranic worldview.